Current standards for syphilis treatment: comparing the russian and foreign guidelines (part II) - T. V. Krasnoselskikh; E. V. Sokolovskiy (State Scientific Center of Dermatovenereology and Cosmetology, 2017)
The introduction of penicillin has been a breakthrough in the treatment of syphilis. For 70 years, penicillin remains the preferred drug for the treatment of all forms of the disease; its effectiveness has been proven by wide experience gained from clinical observations. However, a very limited number of published meta-analyzes, systematic reviews and data from randomized controlled trials on the comparative assessment of the effectiveness of various antibiotics and treatment regimens are currently available. Some aspects of syphilis treatment are insufficiently developed, particularly, the treatment schedules for neurosyphilis, syphilis in pregnancy, syphilis in HIV-infected individuals and persons allergic to penicillin. There are disagreements in the assessment of the clinical significance of serofast state after a course of antibiotic therapy. There is no uniform approach to the management of patients with treatment failures. This article compares the Russian standards for syphilis treatment set out in the «Federal guidelines for the management of patients with syphilis» with the current European recommendations of the International Union against Sexually Transmitted Infections (IUSTI) and the recommendations of the US Centers for Disease Control and Prevention (CDC). The peculiarities of these guidelines, their strengths and shortcomings, as well as controversial issues of syphilis therapy are discussed. The differences between the domestic and foreign recommendations are more significant in the section concerning the treatment of syphilis than in the section of diagnosis.